From brain to spinal cord: neuromodulation by direct current stimulation and its promising effects as a treatment option for restless legs syndrome - Dirks, Christina A. H.; Bachmann, Cornelius G. (Frontiers in Neurology, 2024)
This narrative review offers a concise overview of the potential of transcranial and transcutaneous spinal direct current stimulation in the rapidly growing field of neuromodulation. As with transcranial magnetic stimulation, direct current stimulation also offers a variety of options for non-invasive, non-drug therapy for a wide variety of diseases, many of which are presented in this article. The focus here is on the therapy options that result from the use of transcutaneous spinal direct current stimulation (tsDCS) for the treatment of Restless Legs Syndrome (RLS). For RLS, drug treatment is still the gold-standard, which entails numerous side effects for the patients. Therefore, there is a great need for new, effective, non-drug treatment options. In this article we explain to what extent tsDCS could fill this gap in current therapy options.